1988
DOI: 10.1128/jb.170.12.5789-5796.1988
|View full text |Cite
|
Sign up to set email alerts
|

Selective release of the Treponema pallidum outer membrane and associated polypeptides with Triton X-114

Abstract: The effects of the nonionic detergent Triton X-114 on the ultrastructure of Treponema pallidum subsp. pallidum are presented in this study. Treatment of Percoll-purified motile T. pallidum with a 1% concentration of Triton X-114 resulted in cell surface blebbing followed by lysis of blebs and a decrease in diameter from 0.25-0.35 ,um to 0.1-0.15 ,im. Examination of thin sections of untreated Percoll-purified T. pallidum showed integrity of outer and cytoplasmic membranes. In contrast, thin sections of Triton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
90
0
2

Year Published

1989
1989
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 25 publications
9
90
0
2
Order By: Relevance
“…These organisms are also capable of several biological functions in vitro that correlate with pathogenesis in vivo; they attach to a number of cell types in culture (9) and can penetrate endothelial cell monolayers through tight junctions (30). Our thin-section electron microscopy studies have shown that freshly extracted organisms have intact cross-sectional morphology characteristic of that of the spirochetes (6). Thus, the organisms used in this study represent, by all available biological parameters, virulent, structurally intact T. pallidum.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…These organisms are also capable of several biological functions in vitro that correlate with pathogenesis in vivo; they attach to a number of cell types in culture (9) and can penetrate endothelial cell monolayers through tight junctions (30). Our thin-section electron microscopy studies have shown that freshly extracted organisms have intact cross-sectional morphology characteristic of that of the spirochetes (6). Thus, the organisms used in this study represent, by all available biological parameters, virulent, structurally intact T. pallidum.…”
Section: Resultsmentioning
confidence: 90%
“…Therefore, a quantitative assessment of the degree of OM release was not possible. In our laboratory, Cunningham et al showed by thin-section electron microscopy that 1% Triton X-114 removed the OM of T. pallidum but left the IM morphologically intact (6). After phase partitioning of the Triton-soluble material, a set of eight polypeptides remained in the detergent phase, characteristic of integral membrane proteins.…”
Section: Resultsmentioning
confidence: 99%
“…After centrifugation, Triton X-114 (TX-114; Calbiochem) was added to the supernatant to a final concentration of 1%. The solution was phase partitioned, and the detergent phase was washed three times with cold 50 mM Tris-HCl (pH 8.0) as described previously (20,43,53). The detergent phase was then diluted to 10 ml with 50 mM Tris-HCl (pH 8.0)-0.1% hydrogenated TX-100 (hTX-100) (Calbiochem Corp., San Diego, Calif.).…”
Section: Methodsmentioning
confidence: 99%
“…Phenylmethylsulfonyl fluoride (Fisher), prepared as a 50-mg ml Ϫ1 stock solution in isopropanol, was added to a final concentration of 0.5 g l Ϫ1 , and the cells were harvested by centrifugation (11,228 ϫ g; 4°C), washed with PBS, and immediately resuspended in SDS solubilizing solution containing PMSF (0.5 g l Ϫ1 ). Triton X-114 extraction and phase partitioning was performed as described by Cunningham et al (10). Briefly, exponential-phase cells at an optical density at 600 nm of 0.5 were harvested by centrifugation, resuspended in 1% Triton X-114 (in PBS), and incubated at 4°C overnight with gentle rocking.…”
Section: Vol 186 2004 B Hermsii Plasmid-encoded Factor H-binding Pmentioning
confidence: 99%